Reading and Writing the Latin American Landscape - Rivera-Barnes, B. author. aut Link
VI, 203 p.
Keywords: Spanning the whole of Latin America, including Brazil, from its beginnings in 1492 up to the present time, Rivera-Barnes and Hoeg analyze the relationship between literature and the environment in both literary and testimonial texts, asking questions that contribute to the on-going dialogue between the arts and the sciences.